Pengaruh Sanksi Pajak dan Tax Amnesty Terhadap Keputusan Kepatuhan Wajib Pajak - Meichelle Liman Pratiknjo; Lodovicus Lasdi (Perspektif Akuntansi, 2022)
Tax is one of the sources of state revenue and the spearhead of the state budget. The government seeks to improve tax compliance decisions by implementing tax sanctions and tax amnesty policies. This research is an experimental research which has the aim of knowing the effect of tax sanctions and tax amnesty on taxpayer compliance decisions. This study uses a 2x2 factorial experimental design conducted on undergraduate accounting students at Widya Mandala Catholic University Surabaya who have taken and passed the Taxation II course with a total of 81 participants. Experiments in this study were conducted by distributing google forms randomly to participants. Tests in this research using ANOVA. The results of this study indicate that tax sanctions and tax amnesty affect taxpayer compliance decisions. High tax sanctions tend to increase taxpayer compliance decisions compared to low tax sanctions. The existence of a tax amnesty tends to increase taxpayer compliance decisions compared to the absence of a tax amnesty.